Coagulation FXIII-A Protein Expression Defines Three Novel Sub-populations in Pediatric B-Cell Progenitor Acute Lymphoblastic Leukemia Characterized by Distinct Gene Expression Signatures - Gyurina, Katalin; Kárai, Bettina; Ujfalusi, Anikó; Hevessy, Zsuzsanna; Barna, Gábor; Jáksó, Pál; Pálfi-Mészáros, Gyöngyi; Póliska, Szilárd; Scholtz, Beáta; Kappelmayer, János; Zahuczky, Gábor; Kiss, Csongor (Frontiers in Oncology, 2019)
Leukemic B-cell precursor (BCP) lymphoblasts were recently identified as a novel expression site for coagulation factor XIII subunit A (FXIII-A). FXIII-A expression determined by flow cytometry (FC) exhibited characteristically distinct expression patterns in the subgroups of FXIII-A negative, FXIII-A dim, and FXIII-A bright lymphoblasts. The FXIII-A negative subgroup was significantly associated with the ‘B-other’ genetic category and had an unfavorable disease outcome. RNA was extracted from bone marrow lymphoblasts of 42 pediatric patients with BCP-acute lymphoblastic leukemia (ALL). FXIII-A expression was determined by multiparameter FC. Genetic diagnosis was based on conventional cytogenetic method and fluorescence in situ hybridization. Affymetrix GeneChip Human Primeview array was used to analyze global expression pattern of 28869 well-annotated genes. Microarray data were analyzed by Genespring GX14.9.1 software. Gene Ontology (GO) analysis was performed using Cytoscape 3.4.0 software with ClueGO application. Selected differentially expressed (DE) genes were validated by RT-Q-PCR. We demonstrated, for the first time, the general expression of F13A1 gene in pediatric BCP-ALL samples. The intensity of F13A1 expression corresponded to the expression of FXIII-A protein, as determined by FC. Three well-defined categories of FXIII-A expression: FXIII-A negative, FXIII-A dim, and FXIII-A bright subgroups defined by characteristic and distinct gene expression signatures detected by Affymetrix oligonucleotide microarrays. Relative gene expression intensity of ANGPTL2, EHMT1 FOXO1, HAP1, NUCKS1, NUP43, PIK3CG, RAPGEF5, SEMA6A, SPIN1, TRH, and WASF2, validated by RT-Q-PCR according to the FXIII-A status, followed the pattern of intensity of the expression of the F13A1 gene. PLAC8 was downregulated in the FXIII-A bright subgroup. Gene expression signature of the FXIII-A negative subgroup showed an overlap with the signature of ‘B-other’ samples. DFFA, GIGYF1, GIGYF2, and INTS3 were upregulated and CD3G was downregulated in the ‘B-other’ subgroup. Validated genes proved biologically and clinically relevant. We described differential expression of genes not shown previously to be associated with pediatric BCP-ALL. Gene expression signature according to FXIII-A protein expression status defined three novel subgroups of pediatric BCP-ALL. Multiparameter FC appears to be an easy-to-use and affordable method to help in selecting FXIII-A negative patients who require a more elaborate and expensive molecular genetic investigation to design precision treatment.